FACTORS INFLUENCING THE SUCCESS OF LOCAL STREET FOOD BUSINESSES IN THAILAND’S LOWER CENTRAL REGION - Peeraphatchara, Chutamas; Hirunakrawong, Intheema; Youngworawichian, Patcharanun; Youngworawichian, Patcharanun (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2026)
Street food is closely associated with culture and society and plays an important role in supporting economic activities. This study aimed to 1) examine operational factors of local street food businesses in the Lower Central Region, 2) investigate business success, and 3) analyze the influence of operational factors on business success. The sample consisted of 400 local street food operators in the Lower Central Region 2. Data were collected using a questionnaire and analyzed using descriptive statistics (mean and standard deviation) and inferential statistics through multiple regression analysis with the enter method. The results indicated that overall business operations in terms of health, economic, social, cultural, and innovation dimensions were at a high level (mean = 4.08), with the social dimension showing the highest mean score (4.41). Business success in terms of sales and profit, recommendation, and customer satisfaction was also at a high level (mean = 4.08), with customer satisfaction ranking highest (mean = 4.26). Service quality, online marketing communication, food cleanliness and safety, food uniqueness, and the expression of Thai identity had a statistically significant positive influence on business success, while some operational factors showed negative or varied relationships depending on the success dimension. Overall, the operational factors examined were able to explain approximately 21–30% of the variance in business success. The findings provide empirical evidence for developing guidelines to enhance operators’ capabilities, establishing hygienic street food prototype areas, and supporting further studies on street food businesses under changing economic and social contexts.